Using the modified socio-ecological model to address stigma against non-suicidal self-injury among adolescents in Malaysia - Thum, Chern Choong; Dahlan, Rahima; Wong, Yen Jun (Frontiers Media, 2023)
Non-suicidal self-injury is defined as an intentional injury to one’s body without a desire to cause death. It may involve acts that include, but are not limited to, damaging one’s own skin and self-poisoning for purposes that are not socially sanctioned. In this article, the term “non-suicidal self-injury” (NSSI) and its acronym NSSI are preferred because it is a diagnostic entity in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). NSSI usually follows a behavioral cycle. It often begins with negative emotions such as depression, anxiety, or stress. These emotions can trigger the urge to engage in NSSI, as individuals use self-harm as a coping mechanism to regulate their emotions. This can then trigger a new cycle of negative emotions, vulnerability factors, urges, and self-injury. Breaking the cycle of NSSI can be challenging and often requires the support of mental health professionals and the development of healthy coping mechanisms to regulate negative emotions.